Brain temperature regulation in poor-grade subarachnoid hemorrhage patients – A multimodal neuromonitoring study. Issue 2 (February 2021) - Addis, Alberto; Gaasch, Maxime; Schiefecker, Alois J; Kofler, Mario; Ianosi, Bogdan; Rass, Verena; Lindner, Anna; Broessner, Gregor; Beer, Ronny; Pfausler, Bettina; Thomé, Claudius; Schmutzhard, Erich; et al.
Elevated body temperature (Tcore ) is associated with poor outcome after subarachnoid hemorrhage (SAH). Brain temperature (Tbrain ) is usually higher than Tcore . However, the implication of this difference (Tdelta ) remains unclear. We aimed to study factors associated with higher Tdelta and its association with outcome. We included 46 SAH patients undergoing multimodal neuromonitoring, for a total of 7879 h of averaged data of Tcore, Tbrain, cerebral blood flow, cerebral perfusion pressure, intracranial pressure and cerebral metabolism (CMD). Three-months good functional outcome was defined as modified Rankin Scale ≤2. Tbrain was tightly correlated with Tcore (r = 0.948, p < 0.01), and was higher in 73.7% of neuromonitoring time (Tdelta +0.18°C, IQR −0.01 – 0.37°C). A higher Tdelta was associated with better metabolic state, indicated by lower CMD-glutamate ( p = 0.003) and CMD-lactate ( p < 0.001), and lower risk of mitochondrial dysfunction (MD) (OR = 0.2, p < 0.001). During MD, Tdelta was significantly lower (0°C, IQR −0.2 – 0.1; p < 0.001). A higher Tdelta was associated with improved outcome (OR = 7.7, p = 0.002). Our study suggests that Tbrain is associated with brain metabolic activity and exceeds Tcore when mitochondrial function is preserved. Further studies are needed to understand how Tdelta may serve as a surrogate marker for brain function and predict clinical course and outcome after SAH.